A study of the third English ambassador Henry Lello's report on the Ottoman Empire (1597-1607) - Çeliktemel, Başak (İstanbul Bilgi Üniversitesi, 2012)
This M.A. thesis aims to analyze trans-imperial and diplomatic relations within the framework of English Ambassador Henry Lello’s report (1597-1607) that is set within the multilayered network of administrative systems between the Ottoman Empire and England during the late sixteenth and early seventeenth centuries. Lello’s report is about palace rivalries, suppressions and murders in the Ottoman Empire. The trans-imperial mediators, in other words diplomats, interpreters and merchants, were among the Sultan’s “favourites”. The “favourite” was obliged to serve multiple masters/employers within a multilayered network of obligations. While the “favourite” had critical roles in the trans-imperial administrative system, s/he was concurrently servant of the Sultan and the King/Queen. One of the main goals of my thesis, within the framework of Ambassador Henry Lello’s report, is to examine different levels of master/employer relationships and gift-giving process that was entrenched within the Ottoman cultural tradition and that eventually became a diplomatic requirement in transimperial relations.

Osmanlı İmparatorluğu ve İngiltere’nin imparatorluklararası diplomatik ilişkiler ağına odaklanan bu yüksek lisans tezi, İngiliz elçisi Henry Lello’nun (1597-1607) raporu çerçevesinde geç on altıncı yüzyıl ile erken on yedinci yüzyıllardaki idari sistemin karmaşık ilişkilerini ve yapısını tarihsel bir analizle gözlemlemeyi amaçlamaktadır. Lello’nun raporu, Osmanlı İmparatorluğu saray çevresindeki yarış, baskı ve katledilmeler hakkındadır. İmparatorluklararası aracılar, bir diğer deyişle diplomatlar, çevirmenler ve tüccarlar, Sultan’ın “has adamlar”ından oluşmaktaydı. Bu “has adam”, pek çok efendisine/işverenine karmaşık bir zorunluluklar sistemi dâhilinde hizmet etmekteydi. “Has adam” imparatorluklararası idari sistemde kritik rollere sahipken aynı zamanda, Sultan’ın ve Kral’ın/Kraliçe’nin hizmetkârı da olabilmekteydi. Bu bağlamda tezimin temel amacı, İngiliz elçisi Henry Lello’nun raporu ışığında, Osmanlı İmparatorluğu’nda kültürel geleneğin köklü bir parçası olan ve imparatorluklararası ilişkiler sarmalında bir gerekliliğe dönüşen armağan verme sürecine yoğunlaşarak farklı düzeylerdeki “hizmetkâr ve efendi” ilişkilerini incelemektir.
Üçüncü İngiliz elçisi Henry Lello"nun Osmanlı İmparatorluğu ile ilgili raporu üzerine bir Çalışma (1597-1607)